Resonance of magnetization excited by voltage in magnetoelectric heterostructures. (13th April 2018) - Yu, Guoliang; Zhang, Huaiwu; Li, Yuanxun; Li, Jie; Zhang, Dainan; Sun, Nian
Abstract: Manipulation of magnetization dynamics is critical for spin-based devices. Voltage driven magnetization resonance is promising for realizing low-power information processing systems. Here, we show through Finite Element Method (FEM) simulations that magnetization resonance in nanoscale magnetic elements can be generated by a radio frequency (rf) voltage via the converse magnetoelectric (ME) effect. The magnetization dynamics induced by voltage in a ME heterostructures is simulated by taking into account the magnetoelastic and piezoelectric coupling mechanisms among magnetization, strain and voltage. The frequency of the excited magnetization resonance is equal to the driving rf voltage frequency. The proposed voltage driven magnetization resonance excitation mechanism opens a way toward energy-efficient spin based device applications.